Pengaruh Struktur Modal, Profitabilitas, dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Junia, Dinda Nelandi; Friyani, Rita; Wendry, Widya Sari (Jurnal Akuntansi & Keuangan Unja, 2025)
This purpose of this study is to examine how capital structure, profitability, and company growth on company value in the energy sector listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. This study uses a quantitative approach with purposive sampling techniques, resulting in a sample of energy companies that meet the research criteria. Data were analyzed using multiple linear regression to test the proposed hypotheses. The sample consisted of 51 selected energy companies, and data were processed using SPSS version 27 software. The results indicate that capital structure and profitability significantly influence firm value, while firm growth does not significantly influence firm value. Simultaneously, all three independent variables significantly influence firm value.